Dynamic Connectedness between Renewable and Nonrenewable Energy Consumptions, Economic Growth and Carbon Dioxide Emissions in Vietnam: Extension of the TVP-VAR Joint Connected Approach - Ha, Le Thanh; Huyen, Nguyen Thi Thanh (International Journal of Energy Economics and Policy, 2022)
We employ a time-varying parameter vector autoregression (TVP-VAR) combined with an extended joint connectedness approach to study interlinkages between renewable and nonrenewable energy consumption, economic growth, and CO2 emission by characterizing connectedness of four markets starting from 1985 to 2019. Our results demonstrate that the financial crisis appears to have influences on the system-wide dynamic connectedness, which reaches a peak during 1989. The total directional connectedness suggests that nonrenewable and renewable sources of energy consumption tend to be net recipients of spillover shocks. Throughout the studied period, growth in the economy and CO2 emissions seem to be influential net shock transmitters. Pairwise connectedness reveals that nonrenewable consumption primarily receives spillover effects of economic and environmental shocks. Since the crisis, CO2 emission has been a net receiver of shocks from other variables.